Open Access in Developing Countries: Challenges and Opportunities in Academic Publishing - Nur Achmad; Jamil Khan; Shazia Akhtar (Yayasan Adra Karima Hubbi, 2024)
Challenges such as limited infrastructure, financial constraints, and lack of awareness hinder the effective implementation of open access (OA) initiatives, hindering their continued growth as a means to democratize knowledge and increase research visibility, particularly in developing countries. This study aims to investigate the current state of open access publishing in developing countries, identifying challenges and opportunities that could shape the future of academic dissemination. A mixed-methods approach was used, combining quantitative surveys of researchers and qualitative interviews with key stakeholders, including publishers and policymakers. The study collected data from several developing countries to provide a comprehensive overview of the OA landscape. The findings indicate that while awareness and support for OA publishing are growing, significant barriers remain, including the lack of funding models and inadequate training for researchers on OA practices. The study concludes that fostering a culture of open access in developing countries is crucial for enhancing academic collaboration and information sharing. By addressing identified challenges, such as improving infrastructure and increasing financial support, stakeholders can create a more conducive environment for OA publishing. This study emphasizes the need for collaborative efforts between governments, institutions, and the academic community to harness the potential of open access, ultimately contributing to the advancement of knowledge and research equity in developing countries.